The impact of new incentive schemes on regional competitiveness and comparative advantage of east and west coast paddy production in Peninsular Malaysia - Soh, Norhidayah Che; Ismail, Mohd Mansor; Arshad, Adzemi Mat (Malaysian Society of Applied Biology, 2017)
The food security is a very vital issue in the world and closely related to the rice industry in Malaysia. In 2008, Malaysia and other countries worldwide suffered a devastating food crisis because rice exporting countries experienced widespread natural disasters caused by flooding that destroyed paddy fields. Such incidents demonstrated the importance of enhancing food security seriously. To tackle this issue, Malaysian government had taken drastic action to boost the country’s rice production through a new incentive scheme. The objectives of this study were to assess the private and economic profitability of four major granary areas in the East and West coast of Peninsular Malaysia in 2012/2013 production season using a Policy Analysis Matrix (PAM). Based on the analysis, Muda Agricultural Development Authority (MADA) recorded the highest private profit while Ketara Integrated Agriculture Development Area (IADA KETARA) recorded the highest economic profit. Analysis of comparative advantage based on Domestic Resource Cost (DRC) and Social Cost Benefit (SCB) indicators showed that all areas have comparative advantage and IADA KETARA recorded the highest value. The results also showed clearly that the DRC values were higher after the new paddy incentives.